1990
DOI: 10.1093/oxfordjournals.bmb.a072387
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic drug metabolism and ageing

Abstract: The hepatic clearance of many drugs is reduced in the elderly. Contrary to previously held views we suggest the following: 1. Specific activities of several cytochrome P-450 Phase I enzymes are not reduced with age per se in primate and man, nor is enzyme affinity for substrate changed. 2. An important contribution to the reduced hepatic elimination is made by reduction in liver size and blood flow with advancing age. 3. Major changes in liver drug metabolism may occur in frail old people. Future studies of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(43 citation statements)
references
References 15 publications
0
42
0
1
Order By: Relevance
“…A study based on 1,582 subjects, aged between 20 and 80, was published a decade ago [5]. According to this study, the liver progressively decreased in size with aging and experienced a marked decline in volume occurring after the 6th decade of life as detected by ultrasonography [5]. Wynne et al [6] showed a significant negative correlation between liver volume and age in 65 volunteer subjects aged 24-91.…”
Section: Morphological Changes In Aging Livermentioning
confidence: 99%
See 1 more Smart Citation
“…A study based on 1,582 subjects, aged between 20 and 80, was published a decade ago [5]. According to this study, the liver progressively decreased in size with aging and experienced a marked decline in volume occurring after the 6th decade of life as detected by ultrasonography [5]. Wynne et al [6] showed a significant negative correlation between liver volume and age in 65 volunteer subjects aged 24-91.…”
Section: Morphological Changes In Aging Livermentioning
confidence: 99%
“…In the past, human studies of the aging liver were limited and relied on postmortem samples and often used elderly subjects with liver disease. A study based on 1,582 subjects, aged between 20 and 80, was published a decade ago [5]. According to this study, the liver progressively decreased in size with aging and experienced a marked decline in volume occurring after the 6th decade of life as detected by ultrasonography [5].…”
Section: Morphological Changes In Aging Livermentioning
confidence: 99%
“…Phase I reactions (oxidation, reduction, and hydroxylation) are thought to be affected to a greater extent than phase II reactions (glucuronidation, acetylation, and sulfation). The decrease in oxidative metabolism (cytochrome P450) of some drugs in the elderly is thought to be due to changes in liver blood flow and liver mass as one ages (15). However, based on very limited information, glucuronidation reactions appear to be spared with aging (5).…”
Section: Clinical Pharmacology Of Aeds In the Elderlymentioning
confidence: 99%
“…11 Similarly, the hepatic clearance of many drugs is reduced in the elderly, mainly because of a decrease in liver size (as little as mid-life size 40%) and a reduction in hepatic blood flow. 12 The ageing liver also has a decreased capacity to recover from injury. 13 …”
Section: Pharmacokinetic Changesmentioning
confidence: 99%